The Influence of Compensation, Motivation, Work Discipline on Member Performance at Ditpamobvit Korsabhara Baharkam Polri - Pratama, Andika; Isnanto, Samto Hadi (Dinasti Publisher, 2025)
This study investigates the relationship and impact of compensation, motivation, and work discipline on the performance of members at Ditpamobvit Korsabhara Baharkam Polri. A total of 100 members were sampled, and the data were analyzed using validity and reliability tests, followed by multiple linear regression analysis. The findings indicate that compensation, motivation, and work discipline significantly enhance member performance. This was confirmed through t-tests for each independent variable: the compensation variable showed tcount > ttable ? (5.510 > 1.660) with a significance value of 0.000 < 0.05, leading to the rejection of H0 in favor of Ha, indicating a positive effect. Similarly, for motivation, tcounttcount? was 4.290 > 1.660 with a significance of 0.000 < 0.05, resulting in H0 rejection and Ha acceptance. Work discipline also demonstrated a significant effect with tcount = 4.826 > 1.660, tcount ?= 4.826 > 1.660 and a significance value of 0.000 < 0.05. Furthermore, F-test revealed that together, these variables have a significant influence on performance with Fcount = 156.427 > Ftable =2.70 Fcount ?=156.427 > Ftable ?= 2.70 and a significance value of 0.000 < 0.05, confirming a positive collective impact on member performance.